“You can be the kind of woman that you are”: the discursive management of intersecting identities in leadership talk - Corpuz, Ember; Augoustinos, Martha; Due, Clemence (Psychology: the Journal of the Hellenic Psychological Society, 2023)
The present study investigates how culturally and linguistically diverse (CALD), and Aboriginal and Torres Strait Islander (ATSI) women mobilize intersecting identities through speeches delivered during women in leadership forums. As more women aspire to positions of leadership, the discursive analysis of identity management for understanding how identities are made relevant is critical. Using a discursive psychological approach, this research examines intersectionality as a social action, as it is played out in practice rather than as a theoretical concept. Here it is being anchored to empirical data to explore how it operates in the broader context of leadership talk, in particular, how diverse women represent themselves as leaders and what key identities emerge. The analysis demonstrates that in accounting for how these women achieved leadership positions, the speakers used their multiple identities as strategic resources. These identities included the categories of race, culture, gender, and parenthood. The insights from this study are significant as they shed light on the persisting barriers for women in achieving equal opportunity.